Out of Sync Subnational Housing Markets and Macroprudential Policies in the UK - Michael Funke; Petar Mihaylovski; Adrian Wende (De Economist, 2021)
We examine whether regionally differentiated macroprudential policies can address financial stability concerns and moderate house price differences in the UK. We disaggregate both the household sector and the housing stock in a two-region DSGE model with out of sync subnational housing markets and compare four policy types: standard monetary policy, leaning against the wind monetary policy, national macroprudential policy or one that targets region-specific LTV ratios. In terms of reducing variances of house prices, regionally differentiated macroprudential policy performs best, provided the policy authorities are concerned with stabilising output and house prices rather than simply minimising the variance of inflation.
Keywords: E32; E44; E52; E58; 330; Macroprudential Policies; Housing; DSGE; Great Britain